Religious Legitimation of Early Marriage in Indonesia Through Nusantara Islamic Classical Texts - Isra; Hamka Naping; Ahmad Ismail Guntur; Ahmad Arham Mallu (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
This study explores how religious legitimate early marriage by referring to Nusantara Islamic classical texts (kitab kuning). The study treats kitab kuning not only as collections of legal rules but also as formative religious literature that actively shapes social values and cultural norms. Using textual analysis, critical discourse analysis, and interpretive anthropology, the research examines influential texts such as Uqud al-Lujjayn, Fath al-Qarib, and I’anat al-Talibin. The analysis identifies three central findings. First, the texts themselves display internal ambiguity because they simultaneously promote ethical protection and allow permissive legal interpretations. Second, religious leaders interpret these texts in divergent ways, as some adopt literal readings while others apply contextual approaches. Third, these interpretive choices operate within broader socio-economic and patriarchal power relations that selectively activate textual authority to justify early marriage practices. The study argues that the persistence of early marriage does not stem directly from textual commands. Instead, it emerges from ongoing negotiations among textual ambiguity, interpretive authority, and social structures. By emphasizing this process, the study highlights the decisive role of interpretive communities in managing contradictions within classical texts and stresses the importance of addressing both textual meaning and social context when designing intervention strategies.